The last protector - Taylor, Andrew, 1951 October 14- (HarperCollins Publishers, 2020)
"A dangerous secret lies beneath Whitehall Palace... Brother against brother. Father against son. Friends turned into enemies. No one in England wants a return to the bloody days of the Civil War. But Oliver Cromwell's son, Richard, has abandoned his exile and slipped back into England. The consequences could be catastrophic. James Marwood, a traitor's son turned government agent, is tasked with uncovering Cromwell's motives. But his assignment is complicated by his friend - the regicide's daughter, Cat Lovett - who knew the Cromwells as a child, and who now seems to be hiding a secret of her own about the family. Both Marwood and Cat know they are putting themselves in great danger. And when they find themselves on a top secret mission in the Palace of Whitehall, they realize they are risking their lives...and could even be sent to the block for treason."--